Hyökkäysvauhdin vaikutus maalintekoon jääkiekon suorahyökkäyspelaamisessa tasakentällisin - Heikkilä, Jaakko (2024)
The aim of this study was to determine the impact of high velocity on scoring in ice-hockey rush situations at even strength. Data was collected from all the teams on Finnish SM-League during the season 2022-2023. Teams had 60 games and each one of them produced data automatically for WiseHockey platform where the data was collected and filtered for this study by WiseHockey specialist. The data were analyzed with Jamovi statistical analysis software including independent T-test, one-way Anova, Chi square and Pearson correlation coefficient. Total of 11 397 rush situations were analyzed (velocity, xG, shot result, serial ranking) including 495 goals which were manually analyzed (rush position, middle line, players involved) from video.